The new weapons of the world encyclopedia an international encyclopedia from 5000 B.C. to the 21st century /c The Diagram Group (St. Martin's Griffin, 2007)
This guide covers the entire history of weapons, from the earliest, most primitive instruments up to remarkable advances in modern defense and warfare. Comprehensively illustrated, with diagrams, charts, photographs, and much more.